2018
DOI: 10.1186/s12906-018-2082-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between cold hypersensitivity in the hands and feet and chronic disease: results of a multicentre study

Abstract: BackgroundCold hypersensitivity in the hands and feet (CHHF) is a common symptom in Korea and patients with CHHF complain of coldness in the hands and feet in an environment that is not considered cold by unaffected people. In traditional East Asian medicine, CHHF is believed to be accompanied by various diseases and symptoms, and is considered a symptom that needs active treatment. CHHF is used for pattern identification in the cold pattern, yang deficiency, and constitution. This study aimed to examine the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…In addition, checking underlying diseases and health-risk behaviors should not be omitted. Many suspicious latent diseases have been pointed out in previous studies, including chronic rhinitis, gastroduodenal ulcer, chronic gastritis, sudden hearing loss, thyroid dysfunction, and ocular diseases such as normal tension glaucoma 1,8,20. As health-risk behaviors, we showed that sleep quality of women with cold extremities was poor and they have more habitual drinking.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In addition, checking underlying diseases and health-risk behaviors should not be omitted. Many suspicious latent diseases have been pointed out in previous studies, including chronic rhinitis, gastroduodenal ulcer, chronic gastritis, sudden hearing loss, thyroid dysfunction, and ocular diseases such as normal tension glaucoma 1,8,20. As health-risk behaviors, we showed that sleep quality of women with cold extremities was poor and they have more habitual drinking.…”
Section: Discussionmentioning
confidence: 62%
“…We have examined only women but not men with cold extremities. Although Flammer syndrome occurs in both men and women,12 the prevalence of cold extremities in men was from 22% to 39% in previous studies 1,26. Considering the huge difference between the prevalence in men and women, different findings would be found in men.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…CHHF is considered more important in Korean medicine and other types of traditional East Asian medicine (TEAM) than in Western medicine. This is because CHHF is an important diagnostic factor in TEAM and is traditionally known to accompany several chronic symptoms and diseases, such as dyspepsia, menstrual pain, fatigue, and infertility [8, 9]. Therefore, in TEAM, CHHF is recognized as a symptom that needs to be treated proactively.…”
Section: Introductionmentioning
confidence: 99%